2017
DOI: 10.1007/s12192-016-0754-9
|View full text |Cite
|
Sign up to set email alerts
|

Loss of malin, but not laforin, results in compromised autophagic flux and proteasomal dysfunction in cells exposed to heat shock

Abstract: Heat stress to a cell leads to the activation of heat shock response, which is required for the management of misfolded and unfolded proteins. Macroautophagy and proteasome-mediated degradation are the two cellular processes that degrade polyubiquitinated, misfolded proteins. Contrasting pieces of evidence exist on the effect of heat stress on the activation of the above-mentioned degradative pathways. Laforin phosphatase and malin E3 ubiquitin ligase, the two proteins defective in Lafora neurodegenerative dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…A similar defect in autophagy was later described in malin‐deficient mice ( Epm2b −/−) and in other laforin and malin knockout mice . However, it has been postulated that the impairment in autophagy in LD could be secondary to the accumulation of glycogen , and more recently other groups have even questioned the existence of a general autophagic defect in LD . Here, we found that although an increase in the autophagic response took place, as expected , after treating the cells with CCCP, FCCP or oligomycin plus antimycin A, as well as under starvation conditions (growth in KH medium), the LC3‐II levels were always clearly lower in the fibroblasts from LD patients.…”
Section: Discussionsupporting
confidence: 87%
“…A similar defect in autophagy was later described in malin‐deficient mice ( Epm2b −/−) and in other laforin and malin knockout mice . However, it has been postulated that the impairment in autophagy in LD could be secondary to the accumulation of glycogen , and more recently other groups have even questioned the existence of a general autophagic defect in LD . Here, we found that although an increase in the autophagic response took place, as expected , after treating the cells with CCCP, FCCP or oligomycin plus antimycin A, as well as under starvation conditions (growth in KH medium), the LC3‐II levels were always clearly lower in the fibroblasts from LD patients.…”
Section: Discussionsupporting
confidence: 87%
“…In this research, we studied the impact of USP14 on the apoptosis of HNSCC, and we researched downstream of the USP14-HSF1 pathway. It has been suggested that HSF1 plays an important role in the death of tumor, and it has been reported that HSF1 can regulate the characteristic change of metabolic flux of glycolysis of cancer cells in vivo [52], so the inhibition of HSF1 activity leads slower proliferation and death of tumor cells. Interestingly, the activation of HSF1 has been associated with the upregulation of several antiapoptotic proteins, including Bcl-xL, MCL-1, and Bcl-2, and the survival rate, so the enhanced expression of these antiapoptotic proteins is shown to be mediated by the HSF 1 molecular chaperone HSP protein and BAG3 [53,54].…”
Section: Discussionmentioning
confidence: 99%